A knockout cell library of GPI biosynthetic genes for functional studies of GPI-anchored proteins - Liu, Si-Si; Liu, Yi-Shi; Guo, Xin-Yu; Murakami, Yoshiko; Yang, Ganglong; Gao, Xiao-Dong; Kinoshita, Taroh; Fujita, Morihisa (Communications biology, 2021)
Over 100 kinds of proteins are expressed as glycosylphosphatidylinositol (GPI)-anchored proteins (GPI-APs) on the cell surface in mammalian cells. GPI-APs possess unique properties in terms of their intracellular trafficking and association with lipid rafts. Although it is clear that GPI-APs play critical roles in various biological phenomena, it is poorly understood how the GPI moiety contributes to these mechanisms. More than 30 genes are involved in the correct biosynthesis of GPI-APs. We here constructed a cell library in which 32 genes involved in GPI biosynthesis were knocked out in human embryonic kidney 293 cells. Using the cell library, the surface expression and sensitivity to phosphatidylinositol-specific phospholipase C of GPI-APs were analyzed. Furthermore, we identified structural motifs of GPIs that are recognized by a GPI-binding toxin, aerolysin. The cell-based GPI-knockout library could be applied not only to basic researches, but also to applications and methodologies related to GPI-APs. Liu et al. construct a knock out cell library of genes involved in the biosynthesis of glycosylphosphatidylinositol (GPI)-anchored protein (GPI-APs) from HEK-293 cells and analyzed the surface expression and sensitivity to phosphatidylinositol-specific phospholipase C. Furthermore, the authors also identify structural motifs of GPIs that are recognized by a GPI-binding toxin, aerolysin.